2007
DOI: 10.1590/s1415-52732007000600009
|View full text |Cite
|
Sign up to set email alerts
|

Frutas, legumes e verduras: recomendações técnicas versus constructos sociais

Abstract: Recomendações e prescrições de metas à população, muitas vezes, são construídas apenas com base em definições técnico-científicas, ignorando processos sócio-construtivos dos riscos que envolvem valores, percepções e experiências. Dessa forma, barreiras importantes podem dificultar o avanço de políticas de implementação dessas recomendações. Este artigo apresenta contribuições multidisciplinares à construção de recomendações e metas prescritas, essencialmente no que tange ao consumo de frutas, legumes e verdura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
21

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
0
4
0
21
Order By: Relevance
“…12 A diet focused on the intake of FVG helps to reduce the risks of cardiovascular diseases and cancer, and can also reduce the risk of obesity, diabetes and malignant neoplasms, especially gastrointestinal ones. [12][13] Such scientific evidence has turned into initiatives of promotion of healthy diets, but the results show low rates of adherence from people to this new eating habit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A diet focused on the intake of FVG helps to reduce the risks of cardiovascular diseases and cancer, and can also reduce the risk of obesity, diabetes and malignant neoplasms, especially gastrointestinal ones. [12][13] Such scientific evidence has turned into initiatives of promotion of healthy diets, but the results show low rates of adherence from people to this new eating habit.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that it is necessary to provide new knowledge and give way to popular knowledge, valuing traditions and eating cultures. 3,13 Another reported aspect was the increase in the number of meals and in food intake: [ After the analysis of these statements, we see the adaptations of the mother to the new nutritional demands, especially new times for meals and the increase of food intake.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, lay people take on a fundamental role in deconstructing and reconstructing paradigms and models that are not based only on social fears or technical-scientifi c threats. 7 Many risks, such as chemical contaminations, harmful substances in foods and ailments of civilization still completely escape immediate human perception. The dangers are often neither visible not perceptible to those who are affected and, in certain cases, will not become active during the affected individuals' lifetimes but will have consequences for their descendants.…”
Section: Discussionmentioning
confidence: 99%
“…Em geral, prevalecem padrões altamente energéticos, compostos por refeições rápidas, ricas em gorduras e açúcares simples 11,21 . Nesse cenário, há que compreender melhor a distância existente entre o risco estabelecido pela comunidade científica e o risco reconhecido pela população em geral, no que diz respeito ao consumo de frutas, legumes e verduras, e a manutenção ou promoção de uma alimentação saudável, especialmente na elaboração de políticas públicas em alimentação e nutrição 22 .…”
Section: I S C U S S ã Ounclassified